Effects of drip irrigation system with variation of water source and volume in pepper (Capsicum annuum L.) - Junita Br. Nambela; Krisna Margaretta Malau; Michel Koibur (Jurnal Ilmu Pertanian, 2021)
Water plays the important roles for plants. Besides maintaining the cell turgidity, it also functions as a nutrients solvent for photosythesis process, which affects plant growth. This study aimed to determine the effects of the source and volume of irrigation water with drip irrigation system on the growth of pepper plants in polybags. This research was conducted at the green house of Polbangtan Manokwari, Anday, West Papua from June to October 2020. This research was arranged in a factorial Completely Randomized Design consisting of two treatment factors, namely irrigation water source (PDAM water and ground water) and volume (150 mL per plant, 200 mL per plant, and 250 mL per plant). The results showed that PDAM water showed a better effect than groundwater, while the volume of irrigation water applied to pepper plants had no significant effect on plant height, number of leaves, and stem diameter. This situation is thought to be due to genetic factors from the pepper cultivars grown. PDAM water has a better effect because of its high pH and higher content of Nitrite as N content. Also, it has lower temperature, lower TDS, and lower iron contents. Meanwhile, irrigation water volume of 250 mL per plant per day has a minimal risk of plant drought compared to other treatments.